VACCINATION IN RHEUMATIC DISEASES: AN ALLY OR AN ENEMY? - B. S. Belov (Научно-практическая ревматология)
The importance of comorbid infections in rheumatology has recently increased substantially, particularly due to the introduction of biological agents into clinical practice. One of the ways to solve the above problem is to investigate and actively use different vaccines. The paper deals with the issues concerning the use of vaccines against influenza and pneumococcal infections in rheumatic patients. It discusses the safety and immunogenicity of vaccination in preventing respiratory infections as the most common cause of an adverse outcome in rheumatic diseases. Main areas for future investigations of the considered problem are shown.